Emotion Regulation and Parental Bonding in Families of Adolescents With Internalizing and Externalizing Symptoms - Mannarini, Stefania; Balottin, Laura; Palmieri, Arianna; Carotenuto, Francesco (Frontiers in Psychology, 2018)
Parental bonding and emotional regulation, while important to explain difficulties that may arise in child development, have mainly been studied at an individual level. The present study aims to examine alexithymia and parental bonding in families of adolescents with psychiatric disorders through different generations. The sample included a total of 102 adolescent patients with psychiatric disorders and their parents. In order to take a family level approach, a Latent Class Analysis was used to identify the latent relationships among alexithymia (Toronto Alexithymia Scale), perceived parental bonding (Parental Bonding Instrument) and the presence of adolescent internalizing or externalizing psychiatric symptoms (Youth Self-Report). Families of internalizing and externalizing adolescents present different and specific patterns of emotional regulation and parenting. High levels of adolescent alexithymia, along with a neglectful parenting style perceived by the adolescent and the father as well, characterized the families of patients with internalizing symptoms. On the other hand, in the families with externalizing adolescents, it was mainly the mother to remember an affectionless control parental style. These results suggest the existence of an intergenerational transmission of specific parental bonding, which may influence the emotional regulation and therefore the manifestation of psychiatric symptoms.